The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.32604/cmes.2023.022201
|View full text |Cite
|
Sign up to set email alerts
|

Ranked-Set Sampling Based Distribution Free Control Chart with Application in CSTR Process

Abstract: Nonparametric (distribution-free) control charts have been introduced in recent years when quality characteristics do not follow a specific distribution. When the sample selection is prohibitively expensive, we prefer ranked-set sampling over simple random sampling because ranked set sampling-based control charts outperform simple random sampling-based control charts. In this study, we proposed a nonparametric homogeneously weighted moving average based on the Wilcoxon signed-rank test with ranked set sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The primary goal of this research is to determine IC and OC RL using L sigma limits under the assumption of the Monte Carlo simulation method. Many researchers Abid et al., 22 Noor‐ul‐Amin et al., 23 Aslam and Anwar, 24 Abbasi et al., 12 Rasheed et al., 25 Zhang et al., 26 Almanjahie et al., 27 and Arslan et al 19 . used L sigma limits under Monte Carlo simulation for the performance evaluation of EWMA charts in various setup.…”
Section: Performance Metricsmentioning
confidence: 99%
“…The primary goal of this research is to determine IC and OC RL using L sigma limits under the assumption of the Monte Carlo simulation method. Many researchers Abid et al., 22 Noor‐ul‐Amin et al., 23 Aslam and Anwar, 24 Abbasi et al., 12 Rasheed et al., 25 Zhang et al., 26 Almanjahie et al., 27 and Arslan et al 19 . used L sigma limits under Monte Carlo simulation for the performance evaluation of EWMA charts in various setup.…”
Section: Performance Metricsmentioning
confidence: 99%
“…In the third paper entitled "Ranked-Set Sampling Based Distribution Free Control Chart with Application in CSTR Process" by Almanjahie et al [3], the authors suggested a nonparametric homogeneously weighted moving average for detecting shifts in the process location of a continuous and symmetric distribution based on the Wilcoxon signed-rank test with ranked set sampling control chart.…”
mentioning
confidence: 99%